Juridical Review of the Acts of Vertical Integration and Discrimination Performed by Pt Grab Teknologi Indonesia and Pt Teknolog Pengangkutan Indonesia Regarding Transportation Services Special Rental - Cucuk Endratno (LEGAL BRIEF, 2021)
This study aims to find out the problems regarding the act of vertical integration and discrimination carried out by PT Grab Indonesia and PT Teknologi Pengangkutan Indonesia related to special rental transportation services . This research is a normative juridical legal research with 2 types of approaches, namely the Legislative Approach and the legal concept analysis approach. The type of data used is primary data, namely related laws and regulations, especially Law no. 5 of 1999 concerning the Prohibition of Monopolistic Practices and Unfair Business Competition and secondary data obtained from library materials. The type of analysis used is inductive analysis, which analyzes the laws and regulations related to the problem and then correlates it with several principles and theories that form the basis for writing this thesis. In this writing, the author concludes that the judge's considerations in analyzing the case of the Practice of Vertical Integration and Discrimination carried out by PT Grab Indonesia and PT TPI related to this special rental transportation service used 3 (three) theories, namely, the theory of business competition, the theory of justice, and the theory of protection. law